Peningkatan Kemandirian dan Hasil Belajar Berdiferensiasi Berbasis PBL Pendidikan Agama Katolik SD Santo Fransiskus Sragen - Paulus Supriwidodo; Andarweni Astuti (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
The background of this study is that students have different characteristics, both different levels of intelligence, talents, interests, learning styles and backgrounds. Learning with the same model and method is given to all students causing remedial to occur. Differentiation learning is carried out to meet individual needs based on learning readiness, learning interest, and learning profile. The aim of this research is to apply differentiated learning based on problem base learning to increase the independence of learning at St. Francis Elementary School Sragen in Catholic Religious Education lessons, can further improve learning outcomes. This study applies a descriptive method, through classroom action research in two cycles. The first cycle shows the learning outcomes of students in the proficient category as many as 6 people, 7 people in the competent category, 4 people in the appropriate category, and 1 person in the newly developed category, the learning independence of students is still not optimal as indicated by the learning independence value of 74%. The second cycle showed an increase in value learning outcomes in the proficient category of 7 people, 9 people in the competent category, 2 people in the appropriate category, the independence of students has shown an increase of 88%. The implications of this research greatly affect the independence and learning outcomes of students which can be improved by methods that emphasize activeness through PBL based on differentiation learning.